Analysis of the competition under yield and demand uncertainty with yield-dependent price - Şaşmaz, Özge. (Thesis (M.S.)-Bogazici University. Institute for Graduate Studies in Science and Engineering, 2009., 2009)
In this study, the competition of two manufacturers in a two stage game is analyzed. At the beginning of the first stage, the manufacturers decide on the amount of the area to be leased in the presence of random yield and demand. At the end of this period, the yield is realized and the manufacturers try to optimize their optimum production quantity with respect to the random demand and realized yield. Both the centralized and decentralized game analysis are included in the study. The centralized analysis acts as a benchmark for the decentralized game results. In the centralized analysis, the optimality of the decision variables are discussed and the sensitivity analysis of the decision variables is performed. As far as decentralized analysis is concerned, the unique equilibrium is characterized. Comparative statics results are presented to study the effect of different parameters on the equilibrium. For both centralized and decentralized settings, a computational study is presented. First stage results show that the centralized game expected profit is higher than the sum of the decentralized game expected profits which implies that coordination is necessary. Moreover, if there is a low yield expectation, competitors should consider coordination options more. Another noteworthy result is that as the expected profit is concerned, as maximum capacity of the market increases, inefficiency due to the competition decreases.
Keywords: Competition.; Business logistics.